Law 101 Fundamentals of the Law - Martella, Michael H. (Open textbook library., 2018)
Law 101: Fundamentals of Law, New York and Federal Law is an attempt to provide basic legal concepts of the law to undergraduates in easily understood plain English. Each chapter covers a different area of the law. Areas of law were selected based on what legal matters undergraduates may typically encounter in their daily lives. The textbook is introductory by nature and not meant as a legal treatise.Facebook